A wide and collimated radio jet in 3C84 on the scale of a few hundred gravitational radii. (June 2018) - Giovannini, G.; Savolainen, T.; Orienti, M.; Nakamura, M.; Nagai, H.; Kino, M.; Giroletti, M.; Hada, K.; Bruni, G.; Kovalev, Y.; Anderson, J.; D'Ammando, F.; et al.
Abstract Understanding the formation of relativistic jets in active galactic nuclei remains an elusive problem1 . This is partly because observational tests of jet formation models suffer from the limited angular resolution of ground-based very-long-baseline interferometry that has thus far been able to probe the structure of the jet acceleration and collimation region in only two sources2, 3 . Here, we report observations of 3C84 (NGC 1275)—the central galaxy of the Perseus cluster—made with an interferometric array including the orbiting radio telescope of the RadioAstron4 mission. The data transversely resolve the edge-brightened jet in 3C84 only 30 μas from the core, which is ten times closer to the central engine than was possible in previous ground-based observations5 and allows us to measure the jet collimation profile from 102 to 104 gravitational radii (r g ) from the black hole. The previously found5, almost cylindrical jet profile on scales larger than a few thousandr g is seen to continue at least down to a few hundredr g from the black hole, and we find a broad jet with a transverse radius of≳ 250 r g at only 350 r g from the core. This implies that either the bright outer jet layer goes through a very rapid lateral expansion on scales ≲102 r g or it is launched from the accretion disk. Interferometric observations of 3C84 reveal a broad cylindrical jet a few hundred gravitational radii from the black hole, implying that the jet either undergoes a rapid lateral expansion on even smaller scales or is launched from the accretion disk.